About Brave Princesses and Sensitive Princes: Gender Roles in Folk Tales and in Children's and Youth Literature - Regueiro Salgado, Begoña (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2020)
Now well into the second decade of the 21st century, we are still struggling to achieve equality between men and women and it is doubtless to me that education is the best tool to achieve this equality. The aim of this paper is twofold: 1) to reject the false beliefs that accuse folk tales of promoting sexism; and 2) to offer initial teacher training students a repertoire of folk tales, and other tales of acknowledged literary quality, through which they can access female, male and gender-related models beyond patriarchy types.
Keywords: folk tales; literary education; children's and youth literature; feminism; gender studies